Japan : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that on the back of new policy framework, growth in Japan accelerated sharply in early 2013. First quarter GDP growth rose to 4.1 percent (seasonally adjusted annual rate) after two quarters of stagnation. Rising equity values stimulated consumption, and exports rebounded supported by strong regional demand and a weaker yen. Inflation expectations have started to increase, and actual inflation recorded positive growth in June. The near-term outlook has improved considerably, buoyed by stimulus. In 2014, growth is expected to moderate to 1.2 percent.